Combination Treatment for Extensive Chromoblastomycosis: A Case Report - Khadka, Dhan Keshar; Pandey, Dipayan; Agrawal, Sudha (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Chromoblastomycosis is a chronic and progressive recalcitrant fungal infection of the cutaneous and subcutaneous tissue caused by traumatic inoculation of a specific group of dematiacious fungi through skin. There are different treatment modalities for chromoblastomycosis (medical/surgical) having various efficacy. However, there is no treatment of choice for this disease. Though several therapeutic regimen has been proposed for almost 100 years, the disease may be recalcitrant and almost difficult to eradicate if diagnosed in later stage. Relapses are frequently reported. A combination of various treatment modalities is needed to achieve the best result. We report here a case of chromoblastomycosis in a 62-year-male who presented with verrucous nodules and plaques on right lower limb. The patient was unresponsive to oral itraconazole 400mg daily for 2 months but was subsequently treated with multiple serial sittings of surgical excision and carbon dioxide laser in combination with oral itraconazole over 6 months. This case report focuses on proper management and specifically on differential diagnoses and treatment modalities for chromoblastomycosis. Keywords: carbon dioxide laser; chromoblastomycosis; combination treatment.